Environmental odor perception: testing regional differences on heterogeneity with application to odor perceptions in the area of Este (Italy). Issue 6 (20th May 2015) - Arboretti Giancristofaro, R.; Bonnini, S.; Corain, L.; Vidotto, D.
Abstract : One way to evaluate the hazard of environmental degradation of the quality of life in a place, because of bad odors, is to consider the heterogeneity of possible types and of possible sources of malodors. In the literature, the problem of comparing heterogeneities of types or of sources of odors in two geographical areas has not yet been dealt with the due attention. The main reason is that methodological proposals for tests for heterogeneity comparisons are very rare. We propose a permutation test based on the comparison of linear combinations of sampling indices of heterogeneity. The good power behavior, especially for small differences of the degrees of heterogeneity of the two compared areas, is proved through a Monte Carlo simulation study. The application of the test for heterogeneity comparisons on the data of the survey on odor perceptions in the region of Este (Italy) performed in 2010 shows the usefulness of the proposed methodology, which can be added, as a complementary analysis, to the classical established techniques for studying the environmental impact of odors like dispersion models, dynamic olfactometry, smell maps determination, and others. Copyright © 2015 John Wiley & Sons, Ltd.